Risk Factors of Postpartum Urinary Retention After Vaginal Delivery: A Case-Control Study - Saif, Mahrukh; Farooq, Aqsa; Khurshid, Misbah (Biological and Clinical Sciences Research Journal, 2025)
PPUR is a common yet underdiagnosed complication of vaginal delivery, especially in low-resource settings. Objective: This study aimed to identify maternal and intrapartum risk factors associated with PPUR. Methods: A case-control study was conducted at Ibn-e-Siena Hospital, Multan, over three months from 22 January 2025 to 22 April 2025. A total of 142 women (71 with PPUR, 71 controls) were assessed for maternal characteristics and intrapartum variables. Statistical analysis included logistic regression to identify independent risk factors. Results: Significant independent risk factors for PPUR included episiotomy (OR 3.90), epidural analgesia (OR 3.88), obesity (OR 2.54), gestational diabetes (OR 3.39), macrosomia (OR 4.75), and longer labor duration (p = 0.003) were noted in this study. Conclusion: Targeted monitoring for women with identified risk factors may reduce the incidence and complications of PPUR. These findings support the integration of routine bladder care into postpartum protocols in Pakistani healthcare settings.